Omnichannel Intelligence in Gaming: AI and Mobile Systems for Casino Slot Transformation - Ramachandran, Karthick (International Journal of Computer Sciences and Engineering, 2025)
This paper explores a transformative mobile ecosystem for casino slot management, blending AI-driven personalization, predictive analytics, decentralized identity, and secure cloud-native infrastructure. The proposed framework enhances operational efficiency, data privacy, and player experience through multimodal biometric authentication, personalized offer engines, predictive dispatch, and hybrid AI-cloud architecture. By addressing the limitations of legacy systems and unifying mobile and physical gaming experiences, the system fosters zero-friction interaction, real-time insight, and responsible gambling.